Roma prima del mito : abitati e necropoli dal Neolitico alla prima eta' dei metalli nel territorio di Roma (VI-III millennio A.C.) - Anzidei, A. P.; Carboni, Giovanni, (Archaeopress Archaeology, 2020)
This two-volume study looks at the recent excavations in Rome and its surrounding areas which identified settlements and necropolises associated with a complex culture pre-dating that of Ancient Rome. The results reveal the social and cultural aspects of the daily life of the human groups who occupied this territory before the Latium civilization.